The Islamic Education Policy in Public Junior High Schools - Suryani, Irma; Darimus, Darimus; Asmuri, Asmuri; Fitri , Dina (The Future of Education Journal, 2024)
This study aims to analyze how Islamic education policies in Junior High Schools are designed, implemented, and evaluated in the context of the Independent Curriculum and attempts to identify supporting and inhibiting factors for the implementation of the policy. This study uses Library Research with a qualitative approach. Islamic education policies in Junior High Schools have a strategic role in shaping a generation that is faithful, pious, and has noble character. The implementation of policies in the context of the Independent Curriculum provides an opportunity to integrate Islamic values ​​into the learning process flexibly and contextually. Through effective policies, schools can create an educational environment that supports the development of students' Islamic character, both through strengthening the curriculum, religious activity programs, and social interactions based on Islamic values. The supporting factors for the successful implementation of Islamic education policies in Junior High Schools are a flexible curriculum, teacher competence, parental support, and adequate facilities. Meanwhile, the challenges are limited resources, lack of relevant teaching materials, and the influence of globalization which greatly demands adaptive and innovative strategies so that they can provide maximum impact. So that strategic steps are needed in the future with synergy between the government, schools, parents and the community need to be improved to optimize the implementation of this policy. If all parties have coordinated well, this policy is relevant to the needs of students and is able to produce a generation that excels academically, has an Islamic character, and is ready to face global challenges.